Éloge to Robert Fox - Efthymios Nicolaidis (Studia Historiae Scientiarum)
The 20th Alexandre Koyré Medal awarded since 1968 to prominent historians of science was awarded to Robert Fox, leading historian of European science of the period from the 18th to the beginnings of the 20th century. The Medal was presented to Robert Fox during the 7th International Conference of the European Society for the History of Science, Prague, 23 September 2016, and the Éloge describes his career and work.